Improving STEM program quality in out‐of‐school‐time: Tool development and validation. Issue 2 (9th January 2018) - Shah, Ashima Mathur; Wylie, Caroline; Gitomer, Drew; Noam, Gil
Abstract: In and out‐of‐school time (OST) experiences are viewed as complementary in contributing to students' interest, engagement, and performance in science, technology, engineering, and mathematics (STEM). While tools exist to measure quality in general afterschool settings and others to measure structured science classroom experiences, there is a need for reliable measures of STEM program quality in OST settings such as afterschool programs, summer camps, and museum or science center programming. In this paper we present the development of the Dimensions of Success (DoS) tool, which defines twelve key components of informal, exploratory STEM programming that goes beyond the school day. Additionally, we present a validity argument that includes reliability evidence for the DoS tool based on two studies: Study 1 ( n = 284 observations) and Study 2 ( n = 56 observations). Our findings suggest that the coherence of the constructs and validity evidence, as well as the training and certification procedures in place for DoS, make it an important tool to understand the quality of STEM experiences for youth beyond the school day. A tool like DoS has several implications, including the ability to make national comparisons across programs, create aggregate databases, improve program quality and professional development, as well as to link program quality to student‐level outcomes.